Liberalism, Nationalism and Design Reform in the Habsburg Empire : Museums of Design, Industry and the Applied Arts /: Museums of Design, Industry and the Applied Arts. (2020) - Rampley, Matthew; Prokopovych, Markian; Veszprémi, Nóra
No abstract available